Severe Anti-N-Methyl-D-Aspartate Receptor Encephalitis Under Immunosuppression After Liver Transplantation - Konen, Franz Felix; Schwenkenbecher, Philipp; Jendretzky, Konstantin Fritz; Hümmert, Martin Werner; Wegner, Florian; Stangel, Martin; Sühs, Kurt-Wolfram; Skripuletz, Thomas (Frontiers in Neurology, 2019)
Anti-NMDA receptor encephalitis is a rare and often therapy-responsive autoimmune disease that usually affects young adults and causes neuropsychiatric symptoms. Here, we describe a 69-year-old patient who developed anti-NMDA receptor encephalitis while being under adequate immunosuppressive therapy following liver transplantation. Although a broad spectrum of different immunotherapies was applied and anti-NMDA receptor antibody titers gradually decreased, the clinical course could not be affected positively. Autoimmune encephalitis after transplantation is only described in a few cases and not well-recognized. Our case adds further evidence for anti-NMDA receptor encephalitis as the cause of neuropsychiatric symptoms even under immunosuppressive therapy in a post-transplant setting.